Cotton Seed Bio-Based Metal Working Fluid for Sustainable Machining Operation - Hassan, S. I.; Lawal, S. A.; Adeyemi, K. O.; Adamu, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This work investigated the viability of cottonseed oil as bio-based oil as a contribution to meeting the challenges of developing green industrial materials that are environmentally friendly and sustainable alternatives for use as metal cutting fluid, as many of the conventional metal working fluids were established to be harmful and hazardous both to the environment and health of the operator. The tests revealed that the metal working fluid properties of cottonseed oil were: pH-value, 4.37; viscosity, 33.85 mm2/s at 40 ºC, and 7.89 mm2/s at 100 ºC; density, 0.911 g/cm3; and a flash point of 263 ºC. This result shows that some of these properties compare favourably with those of the conventional mineral oil. It was concluded that at the lower temperature of 40°C the oil is still viscous enough and therefore is suitable for lower temperature operation such as low speed cutting, smaller depth of cut etc., while at a higher temperature of 100°C, the oil becomes less viscous and is thus not viable for higher temperature machining operations such as high-speed cutting operation and larger depths of cut; the density shows that cottonseed oil has high lubricity; the oil is acidic in nature and therefore would require addition of anticorrosive agents to function as a metal working fluid; and that the flash point of the oil is higher than that of the conventional mineral metal working fluid and so can be adjudged to be a very good candidate for the production of bio-based metal working fluid. The analysis indicated that the cottonseed oil, if significantly improved with the use of additives and chemically modified seeds, can be one of the potential candidates to substitute the conventional mineral oil in machining industry.